Sensitivity of the International Skating Union`s mathematical criteria to flag potential scoring anomalies - Looney, M. A.; Howell, S. M. (Measurement in Physical Education and Exercise Science, 2015)
This article describes the "mathematical criteria" employed by the International Skating Union (ISU) to identify potential judging anomalies within competitive figure skating. The mathematical criteria have greater sensitivity to identify scoring anomalies for technical element scores than for the program component scores. This article provides illustrations of how hypothetical subtle judging biases could not be flagged for two female skaters at the 2014 Winter Olympics. As a result, we offer four suggestions to improve the sensitivity of the ISU`s mathematical criteria: (1) alter the way the Total Deviation Points are computed for the program component scores (i.e., use "absolute" error); (2) lessen the amount of error allowed on average for each program component; (3) reconsider the cut-off value for Total Deviation points for the technical elements; and (4) reduce the cut-off value for the range of program component scores. Moreover, we suggest that "absolute" error is a more appropriate descriptor for which both technical element and program component scores can be flagged for potential judging anomalies.